New forgery attack on the authenticated cipher SCREAM and iSCREAM - Yu-dan TIAN; Yong-zhuang WEI (网络与信息安全学报)
Authentication encryption algorithms have been widely used in networks security system since these al-gorithms can efficiently provide both privacy and integrity measurement for data transmission. Recently, authentica-tion encryption algorithms have received attentions extensively since the event of CAESAR cipher solicitation was developed. SCREAM had been selected as one of the second-round candidates in CAESAR competition because of its novel structure and design idea. Currently, the security issue of SCREAM becomes an interesting research topic. Based on the characteristic of SCREAM variable parameters, a new forgery attack was proposed by using the basic idea of the sum collision. In particular, this attack could also be used to iSCREAM algorithm. Different to the best known attacks, the new attack requires less time and data complexities. It is shown that this new attack is more flexible and effective. Furthermore, the success probability of the forgery will be one.